MESSENGER X-ray observations of magnetosphere–surface interaction on the nightside of Mercury. (June 2016) - Lindsay, S.T.; James, M.K.; Bunce, E.J.; Imber, S.M.; Korth, H.; Martindale, A.; Yeoman, T.K.
Abstract: The recently completed MESSENGER mission to Mercury has detected X-ray fluorescence events on the nightside surface of the planet, induced by the precipitation of electrons. We expand upon previously reported catalogues of such events, using a filter based on elemental fluorescence lines to construct a catalogue covering the full five years of the MESSENGER mission. We find that the locations of the majority of these events are ordered in two clear latitudinal bands on the dawn side of the planet centred at ~50°N and ~20°S. Electron precipitation is implied to be either stable or occurring repeatedly on timescales of up to several minutes, long in relation to characteristic times of the Mercury magnetospheric environment. Conversely, X-ray fluorescence events are observed on only ~40% of MESSENGER orbits, although we note that some events are inevitably lost during the filtering process. We suggest that the regions of most intense precipitation are determined by the location of the relevant magnetic field line footprints on the surface. We are able to place speculative limits on the energies of electrons precipitating in this manner based on fluorescence lines in the observed X-ray spectra. The poleward boundaries of the regions of most intense precipitation are found to be collocated with the open-closed field line boundary. We use a magnetic field model to trace field lines from these fluorescence sites to implied locations of origin in the magnetotail. Abstract : Highlights: MESSENGER XRS has observed X-ray fluorescence events on the nightside of Mercury. In the absence of solar X-ray flux this fluorescence must be induced by electrons. We present a catalogue of these events covering the whole MESSENGER mission. Surface locations of the events form patterns reflecting magnetic field structure. We use a magnetic field model to trace the electrons back to the magnetic equator.